MicroRNAs in cancer therapeutic response: Friend and foe - Xue, Jingyan (Baishideng Publishing Group Inc, 2014)
Cancer initiation and development engage extremely complicated pathological processes which involve alterations of a large number of cell signaling cascades and functional networks in temporal and spatial orders. During last decades, microRNAs (miRNAs), a class of non-coding RNAs, have emerged as critical players in cancer pathogenesis and progression by modulating many pathological aspects related to tumor development, growth, metastasis, and drug resistance. The major function of miRNAs is to post-transcriptionally regulate gene expression depending on recognition of complementary sequence residing in target mRNAs. Commonly, a particular miRNA recognition sequence could be found in a number of genes, which allows a single miRNA to regulate multiple functionally connected genes simultaneously and/or chronologically. Furthermore, a single gene can be targeted and regulated by multiple miRNAs. However, previous studies have demonstrated that miRNA functions are highly context-dependent, which leads to distinct pathological outcomes in different types of cancer as well as at different stages by alteration of the same miRNA. Here we summarize recent progress in studies on miRNA function in cancer initiation, metastasis and therapeutic response, focusing on breast cancer. The varying functions of miRNAs and potential application of using miRNAs as biomarkers as well as therapeutic approaches are further discussed in the context of different cancers.